PENGELOLAAN FASILITAS OBJEK WISATA CAGAR BUDAYA MAKAM RAJA KECIK DI DESA BUANTAN BESAR KABUPATEN SIAK - Ahmad Huda; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study aims to determine how the facility management of cultural heritage attractions tomb of King Kecik village of Great Buantan Siak Riau Province.In this study the research methods that I use is a qualitative method with descriptive approach, where researchers tried to describe the actual condition or state by collecting data and information in the field and explain in narrative form without test hypotheses or make predictions before. While data collection techniques in this study using observation, interviews and documentation.Based on the research that has been done, the management of the tomb of King Kecik already well underway just that there are still some facilities that are not functioning optimally and there are still some unmet facilities such as places to eat, drink, where the sale of souvenirs and so forth.Keywords: Facilities Management, Facilities Attractions, Tomb Kings Kecik